Integration of Zakatnomics in Social Community Philanthropy for Improving the Welfare of Low- Income Communities (Study: Teman Peduli Community, Subang Regency) - Febri Ramadhani; Suharto Suharto (Universitas Alma Ata, 2025)
Introduction: Subang is one of the regencies located in West Java Province. The majority of the area consists of plantations and rice fields. However, unfortunately, the potential of Subang Regency is not accompanied by strong socio-economic capabilities, as evidenced by the still high unemployment and poverty rates. A solution for improving the welfare of low-income communities is to integrate it with Zakatnomics. One of the management approaches is through philanthropic institutions such as the Teman Peduli social community. This study aims to explore the role of Zakatnomics in increasing the income of low-income communities.Method : The method used is a qualitative approach with in-depth interviews. The interview results are analyzed using the explanation building technique.Result : The results of the study are that the Teman Peduli aims to increase income and empower low-income communities through two programs: consumptive programs such as help sick people and mass circumcision, and productive programs such as the help grocery store, smart kids program, and assistance in obtaining a health cards These three aspectsâ€”economy, education, and healthâ€”can serve as indicators in achieving a decent standard of living and contribute to the formation of empowered communities.Conclusion :Zakatnomics implemented by the Teman Peduli community is able to increase income and empower low-income communities.Â